The Impact Of Zakat Distribution On Achieving Prosperity (A Case Study Of Baznas Bogor) - Qadryani, Sitti; Ayuniyyah, Qurroh; Supriyanto, Trisiladi (Al-Infaq: Jurnal Ekonomi Islam, 2024)
Zakat is not merely about addressing the short-term needs of mustahik, particularly the poor, but aims to provide sustainable welfare by addressing the root causes of poverty. The success of zakat distribution is often reflected in improvements in mustahik welfare, such as enhanced business performance, fulfillment of daily needs, better health, and access to education. This study examines the zakat distribution programs and their impact on mustahik welfare, focusing on 76 mustahik respondents in Bogor Regency through a quantitative approach using simple linear regression analysis. The findings highlight BAZNAS Bogor Regency's programs, including Bogor Taqwa, Healthy Bogor, Smart Bogor, Bogor Cares, and Bogor Prosperous. The results show that zakat distribution has a significant positive impact on mustahik welfare, with a significance value below 0.05 and an R-squared value of 0.3212, indicating that 32.12% of the variations in mustahik welfare can be attributed to zakat distribution, while the remaining 67.88% is influenced by other factors outside the research model.